Preparation of biodegradable polymer blended of poly(L-lactic acid) /cellulose acetate films in the solvent mixture - C. Witthayaprapakorn (2018)
Nowadays, bio-plastic is the most popular in packaging field. Green chemistry and environmental responsibility has led it to develop the bio-plastic for use as packaging. Polylactic acid (PLA) is the well known staring material in this area. However, some properties of PLA films have to develop. Polymer blend is the interesting technique, in this work, PLA/Cellulose acetate (CA) blend films were prepare by casting solution at various compositions. Mixing solvent of Chloroform and acetone in acid condition were used, it was found that the mixing solvent can improved the compatibility and mechanical properties of the blend films. From this work CA can significantly increase PLA properties both the usefulness and the possible applications for bioplastic material. © (2013) Trans Tech Publications, Switzerland.